JEREMIAH 8:8:: WHY ARE SCRIBES ACCUSED OF CORRUPTING THE TORAH? - Bosman, H L (Acta Theologica, 2018)
Why are scribes accused, in Jeremiah 8:8-9, of corrupting the “tôr?h”? The article contemplates possible answers to this question against the background of what is presupposed in the Book of Jeremiah with regards to “tôr?h” and being a scribe. Does this confront one with a response triggered by the reformation of Josiah (older interpretation) or by an indication of what took place much later during the gradual combination of Torah and Nebi’im as authoritative scripture in Persian and Hellenistic times (recent interpretation)? The article distinguishes between oral common law and written statutory law, in order to rectify anachronistic interpretations of all biblical laws as statutory laws (Berman 2014). The change from oral to written law, facilitated by the scribes, caused a legitimacy crisis and can be explained against the background of a new understanding of what “word of God” or “revelation” entailed (Van der Toorn 2013).